The Use of Eye-Tracking Technology in Pediatric Orofacial Clefts: A Systematic Review and Meta-Analysis - Ghalia Y. Bhadila; Dana A. Alyafi (MDPI AG, 2023)
This systematic review and meta-analysis assessed the quality of the peer-reviewed literature and evaluated the usefulness of eye-tracking technology in evaluating observers' perceptions of pediatric patients with orofacial clefts. PubMed, Science Direct, Wiley, and Web of Science were searched. Articles were screened in accordance with the Preferred Reporting Items for Systematic Review and Meta-analysis guidelines, and their methodological quality was assessed. Of the 10,254 identified studies, 12 were included. Eleven studies were cross-sectional, and one was a prospective cohort study. The main areas of interest analyzed were the eyes, nose, and mouth. Nine studies used assessment scales to analyze the link between perceived attractiveness and visualization patterns and measures. For the fixation duration outcome, six studies were eligible for inclusion in the meta-analysis. All studies reported on fixation duration in milliseconds and reported on a standard deviation. The meta-analysis demonstrated a significant difference in the measurements between the control groups and the patients with orofacial clefts. This might indicate the usefulness of eye-tracking technology as a metric for assessing the success of cleft repairs based on the perceptions of different populations. Future studies should be comprehensively reported on for comparability and reproducibility purposes.